Monitoring online corporate reputation : Assessment of media monitoring tools - Määttä, Tiina (My University, 2021)
Corporate reputation has been described as one of the most important intangible assets of a company. Besides a company’s strategic decisions and personal experiences, corporate reputations are increasingly influenced by information shared in the online environment. However, this supply of information can also be used to gather information about online corporate reputation, meaning the representation of multiple stakeholder’s perceptions of a company derived from online data. Social and online media monitoring tools are developed to gather company-related information from online data, and hence, can be viewed as an opportunity to monitor online corporate reputation. The purpose of this study is to evaluate the functionality of existing monitoring tools in collecting relevant data about online corporate reputation. The research problem is approached via qualitative research methods, and a total of six expert interviews and content analysis are conducted. The expert interviews tackle the influence of the online environment on corporate reputation, identifying the dimensions of corporate reputation and the use and limitations of monitoring tools. In the content analysis, instead, the data sources and capabilities of monitoring tools are elucidated. A comprehensive theoretical background of corporate reputation and monitoring tools is used to replenish the empirical findings and map out what is known about the topic. The findings of this study conclude that as the dimensions of corporate reputation are, at least to some extent, consistent with the information collected by monitoring tools, these tools can be used to collect information about online corporate reputation. It is, however, acknowledged that monitoring tools have several limitations related to data reliability, data collection, and data analysis. These limitations must be taken into account if monitoring tools are used to collect data on online corporate reputation.

Mainetta pidetään yhtenä yritysten tärkeimmistä aineettomista eduista. Strategisten päätösten ja henkilökohtaisten kokemusten lisäksi yritysten maineeseen vaikuttaa yhä etenevissä määrin verkkoympäristössä jaettu informaatio. Verkkoympäristössä jaettua informaatiota voidaan kuitenkin myös hyödyntää yritysten näkökulmasta ja sen avulla voidaan kerätä tietoa yrityksen verkossa ilmentyvästä maineesta eli siitä, millainen yrityksen sidosryhmien näkemys yrityksestä on verkkoympäristöstä kerätyn tiedon perusteella. Sosiaalisen ja verkkomedian seurantatyökalut on kehitetty keräämään tietoa yrityksistä verkkoympäristössä ja näin niiden hyödyntäminen maineen seuraamiseen voidaan nähdä mahdollisuutena. Tämän tutkimuksen tarkoituksena on selvittää, voitaisiinko verkkomaineesta kerätä tietoa seurantatyökaluja hyödyntämällä. Tutkimusongelmaa lähestytään kvalitatiivisia tutkimusmenetelmiä hyödyntäen ja empiirinen aineisto perustuu kuuteen asiantuntijahaastatteluun ja sisällönalyysiin. Asiantuntijahaastatteluissa käsitellään maineen dimensioita, seurantatyökalujen käyttöä ja rajoitteita sekä sitä, millaisia vaikutuksia verkkoympäristöllä on yritysten maineeseen. Sisällönanalyysi puolestaan pureutuu siihen, mitä tietolähteitä seurantatyökalut hyödyntävät ja millaista tietoa niiden avulla voidaan kerätä verkkoympäristöstä. Empiiristä aineistoa täydentää kattava teoriaosuus, jonka avulla luodaan ymmärrys siitä, mitä aiheesta tiedetään jo aiempien tutkimusten perusteella. Koska tutkimuksessa tunnistetut maineen dimensiot vastaavat osittain seurantatyökalujen keräämää tietoa, voidaan todeta että seurantatyökalut soveltuvat yleisellä tasolla tiedon keräämiseen verkkomaineesta. Tuloksissa on kuitenkin otettava huomioon, että seurantatyökaluissa on useita tiedon luotettavuuteen, keräämiseen ja analysointiin liittyviä rajoituksia. Nämä rajoitteet on otettava huomioon, jos seurantatyökaluja halutaan hyödyntää tiedon keräämiseen verkkomaineesta.
Keywords: online media monitoring, online corporate reputation, verkkomedian monitorointi, maine verkkoympäristössä